2019
DOI: 10.1186/s13765-019-0471-z
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring Piper plant amides potential in agricultural and pharmaceutical industries: perspectives of piperine and piperlongumine

Abstract: Piperaceae plants consist of about 3600 species, of which about 2000 are Piper plants. Their habitat is distributed across pantropical regions. The representative plant is Piper nigrum, known as black pepper. These plants have been widely used in folk medicine in Korean traditional medicine. This review collected papers identifying and separating the amides obtained from these Piper plants, with a focus on Piper amides potential to control the production and growth of fungal strains that cause plant disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…These compounds increase shelf life of processed meat products, and may also exert some beneficial effects on human health as suggested by their in vitro biological properties [ 27 ]. More particularly, piperine was shown to have cytotoxic effects on cancer cells [ 27 ] and its blood levels have been associated with lower risk of breast cancer in epidemiological studies [ 28 , 29 ]. On the other hand, piperine levels in blood were found to be associated with an increased risk of diabetes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds increase shelf life of processed meat products, and may also exert some beneficial effects on human health as suggested by their in vitro biological properties [ 27 ]. More particularly, piperine was shown to have cytotoxic effects on cancer cells [ 27 ] and its blood levels have been associated with lower risk of breast cancer in epidemiological studies [ 28 , 29 ]. On the other hand, piperine levels in blood were found to be associated with an increased risk of diabetes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites showed very high intensities in the sausage digests compared to non-processed meat digests. These compounds increase shelf life of processed meat products, and may also exert some beneficial effects on human health as suggested by their in vitro biological properties [27]. More particularly, piperine was shown to have cytotoxic effects on cancer cells [27] and its blood levels have been associated with lower risk of breast cancer in epidemiological studies [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…As reported in several studies, ROS generation in excess interferes with various signaling pathways of the cells [54][55][56][57]. Additionally, JNK of the MAPK family plays a pivotal role in regulating autophagy [58][59][60].…”
Section: Celastrol Induces Autophagy and Promotes G2/m Phase Arrest Vmentioning
confidence: 95%
“…antibacterial and antioxidative effects (16)(17)(18)(19). In particular, the observed anticancer effects of herbal mixture extracts have included their ability to boost the efficacy of standard chemotherapies and reduce side effects during chemotherapy (16).…”
Section: Synergistic Effect Of the Herbal Mixture C5e On Gemcitabine mentioning
confidence: 99%
“…Several studies have reported that extracts of herbal mixtures are excellent agents for the treatment of various types of disease, including cardiovascular and Alzheimer's disease and dermatitis ( 13 15 ). For example, extracts of herbal mixtures have been shown to exhibit anticancer, anti-inflammatory, antibacterial and antioxidative effects ( 16 19 ). In particular, the observed anticancer effects of herbal mixture extracts have included their ability to boost the efficacy of standard chemotherapies and reduce side effects during chemotherapy ( 16 ).…”
Section: Introductionmentioning
confidence: 99%